CEGAH STUNTING DARI HATI : PENGENALAN GIZI SEIMBANG DENGAN KEGIATAN ISI PIRINGKU DI DESA KARANGDOWO PEKALONGAN - Adinda Rakhmania Putri; Hani Ulfiana Maghfiroh; Hasna Amelia Agustin; Yenky Andrianto; Mohammad Irsyad (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
Stunting is a chronic nutritional problem that remains a public health challenge in Indonesia, including in rural areas. Children who experience stunting are at risk of physical growth disorders, cognitive development disorders, and reduced productivity in the future. This community service activity was carried out in Karangdowo Village, Kedungwuni District, with the aim of educating the community about the causes, risks, and efforts to address stunting. The methods used included counseling, interactive discussions, and practical introduction to the “Isi Piringku” (My Plate) concept as a guide to balanced nutrition. The results of the activity showed an increase in the understanding of parents and posyandu cadres about the importance of nutritional intake, proper parenting, and monitoring child growth and development. Through this activity, it is hoped that the people of Karangdowo Village will be able to prevent stunting in a sustainable manner with the support of families, health workers, and the surrounding environment.